Konsep Keseimbangan dalam Ekonomi Syariah: Telah terhadap Nilai Maqashid Syariah - Budi Rohman; Agustia Handayani; Hengki Irawan (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2025)
Sharia economics is built on the foundation of balance (tawazun), which is a fundamental principle in every aspect of economic life. This study aims to analyze the concept of balance in sharia economics through the perspective of maqashid sharia as the highest goal of Islamic law. The research method uses a qualitative approach with library research on classical and contemporary Islamic economic literature. The results show that balance in sharia economics encompasses the material-spiritual, individual-social, worldly-afterlife, and production-distribution dimensions, all integrated within the maqashid sharia framework. The five principles of maqashid sharia (hifzh ad-din, hifzh an-nafs, hifzh al-aql, hifzh an-nasl, and hifzh al-mal) serve as parameters in realizing economic justice and social welfare. The implementation of this concept of balance is relevant in addressing modern economic problems such as inequality, excessive materialism, and resource exploitation.